PREDICTION OF ATTITUDE PERSON DEALING WITH APPLICATIONS WITH ADOBE FLASH CS4 CONFLICT PROFFESIONAL - Ignatius Judo Pamungkas; Diyah Ruri Irawati, SKom, MMSI (Jurnal Sistem Informasi, 2010)
Scientific writing is about an attitude Prediction Applications Someone Facing the Conflict. This application is made to find out how the attitude of every person when faced with conflict.  In scientific writing Attitude Prediction Applications Someone Facing these conflicts, the author uses the Adobe Flash CS4 Professional which can support in terms of presenting information. By using Adobe Flash CS4 Professional, the authors can also be more creative in terms of animation so hopefully attract more users of this application.